Predictors of Viremia in Postpartum Women on Antiretroviral Therapy. (1st January 2020) - Hoffman, Risa M.; Warshaw, Meredith G.; Amico, K. Rivet; Pilotto, Jose; Masheto, Gaerolwe; Achalapong, Jullapong; Machado, Elizabeth; Chokephaibulkit, Kulkanya; Duarte, Geraldo; João, Esau; Graham, Kathleen K.; Knapp, Katherine M.; et al.
Abstract : Background: HIV-infected, postpartum women on antiretroviral therapy (ART) have high rates of viremia. We examined predictors of postpartum viremia in the PROMISE study. Methods: Women with pre-ART CD4 + T-cell counts ≥400 cells/mm 3 who started ART during pregnancy were randomized postpartum to continue ART (CTART) or discontinue ART (DCART). Viral load and self-reported adherence were collected every 12 weeks, up to 144 weeks. Women in DCART reinitiated therapy when clinically indicated. Viremia was defined as 2 consecutive viral loads >1000 copies/mL after 24 weeks on ART. Adherence was dichotomized as missing versus not missing ART doses in the past 4 weeks. Predictors of viremia were examined using Cox proportional hazards regression with adherence as a time-varying covariate. Results: Among 802 women in the CTART arm, median age at entry was 27 years and median CD4 + T-cell count 696 cells/mm 3 . Of 175 women in CTART with viremia (22%), 141 had resistance data, and 12% had resistance to their current regimen. There was an estimated 0.12 probability of viremia by week 48 and 0.25 by week 144. Predictors of viremia included missed ART doses within the past 4 weeks, younger age, shorter duration of pre-entry ART, and being from the South American/Caribbean region. Of 137 women in DCART who reinitiated therapy, probability of viremia was similar to CTART (0.24 by week 96; 0.27 by week 144). Conclusions: Rates of postpartum viremia are high and viremia is more likely in younger postpartum women who start ART later in pregnancy. Interventions should target these higher-risk women. Abstract : Supplemental Digital Content is Available in the Text.